Effect of sex on vaccination outcomes: important but frequently overlooked. (August 2018) - Harper, Alice; Flanagan, Katie L
Highlights: Sex differences in immune responses to vaccination are widely reported. These include sex differences in innate responses, antibodies and T cell responses. There are also sex differences in adverse events and non-targeted vaccine effects. Key mechanisms include effects of sex hormones and sex-linked immune response genes. Sex differences in epigenetics and the microbiota may also play a role. Abstract : It is well established that vaccination does not affect males and females equally. For example, females generally mount greater antibody responses to vaccination than males, but also suffer more adverse events following vaccination, probably as a result of more robust immunity. Despite this, most researchers in the field of vaccinology do not take biological sex into account when conducting their studies. This omission is likely to lead to a loss of important information in terms of both reactogenicity and immunogenicity following vaccination as well as those suffering adverse events. It also suggests that the vaccine dose in males and females may need to be different in order to achieve the same outcome of protective immunity while minimising reactogenicity.